Coronectomy of Deeply Impacted Lower Third Molar: Incidence of Outcomes and Complications after One Year Follow-Up - Jimoh Olubanwo Agbaje; Guido Heijsters; Ahmed Sobhy Salem; Sarah Van Slycke; Serge Schepers; Constantinus Politis; Luc Vrielinck (Stilus Optimus, 2015)
Objectives: The purpose of present study was to assess the surgical management of impacted third molar with proximity to the inferior alveolar nerve and complications associated with coronectomy in a series of patients undergoing third molar surgery. Material and Methods: The position of the mandibular canal in relation to the mandibular third molar region and mandibular foramen in the front part of the mandible (i.e., third molar in close proximity to the inferior alveolar nerve [IAN] or not) was identified on panoramic radiographs of patients scheduled for third molar extraction. Results: Close proximity to the IAN was observed in 64 patients (35 females, 29 males) with an impacted mandibular third molar. Coronectomy was performed in these patients. The most common complication was tooth migration away from the mandibular canal (n = 14), followed by root exposure (n = 5). Re-operation to remove the root was performed in cases with periapical infection and root exposure. Conclusions: The results indicate that coronectomy can be considered a reasonable and safe treatment alternative for patients who demonstrate elevated risk for injury to the inferior alveolar nerve with removal of the third molars. Coronectomy did not increase the incidence of damage to the inferior alveolar nerve and would be safer than complete extraction in situations in which the root of the mandibular third molar overlaps or is in close proximity to the mandibular canal.